Analysis of Strategic Planning and Implementation of Information System Using Ward and Peppard - Muhibah L; Susanty W (Bandar Lampung University (UBL), 2017)
Consider any potential future that will be faced by the organization, strategic planning information systems can help to anticipate the development of information technology in the future. To answer the above conditions and problems, then here I do resume journal entitled